BENTUK PENYAJIAN DAN STRUKTUR GERAK TARI LAGE PANGALASAN DI SANGGAR PAMANAH RASA PANDEGLANG BANTEN - Santo, Aris; Permanasari, Alis Triena; Permana, Rian (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2024)
ABSTRACTThe background of this research is the form of presentation and the structure of the movement of the Lage Pangalasan dance. The purpose of this study was to determine the form of presentation and the movement structure of the Lage Pangalasan dance. The method used is a qualitative descriptive method, with the research object being the Pamanah Rasa Pandeglang Studio. Data collection techniques include library study techniques, observation, interviews and documentation. Data analysis techniques using data reduction, data presentation and data inference. Based on the results of the study, the Lage Pangalasan dance originates from traditional dance arts in Pandeglang Regency which has a form of presentation with elements of movement, music, make-up, clothing and property. The dance movements are taken from the activities of melinjo farmers with pure types of movements and meaningful movements, accompaniment using traditional musical instruments such as calung, kendang, goong, bonang, suling, saron dan angklung. . Cosmetology uses a type of corrective makeup. The clothing used is a dance dress depicting melinjo farmers. with kaneron bag properties. The movement structure consists of 39 main movements and 2 transitional movements. One of the main moves  mempruk, meber panangan, calik and transitional motion includes mincit and trisi.Key words: Form of presentation and structure of motion, Lage Pangalasan